2020
DOI: 10.29408/veles.v4i2.2554
|View full text |Cite
|
Sign up to set email alerts
|

Teacher’s Perception on SQ4R in English Reading Comprehension Learning Using Zoom Application

Abstract: Learning strategy has an important role in the English reading comprehension learning process. To comprehend the text, reading strategy focuses on students’ critical learning. The aims of the study to get teachers’ perception of SQ4R strategy application in English reading comprehension class through zoom application. The method of study used descriptive qualitative. The process of collecting data used observation and questionnaire. The data is taken from the teacher that taught English Reading Comprehension s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…In addition, the SQ4R method can be one good solution to the problems of selecting methods for teaching reading. This is in fact in line with some empirical evidence of the importance of the SQ4R method as one of the effective ways to enhance EFL learners ' reading comprehension (Alzu'bi, 2020;Ginting et al, 2021;Khusniyah, 2020;Mohamed Sayed Mohamed, 2020;Nurhidayat & Suwandi, 2021;Başar & Gürbüz, 2017;Khusniyah & Lustyantie, 2017;Herwanis et al, 2021;Simbolon et al, 2020;Rojabi, 2020). Qualitatively, EFL learners under study experienced EFL reading comprehension process by stepping into six phases, i.e., survey, question, read, recite, relate and review.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In addition, the SQ4R method can be one good solution to the problems of selecting methods for teaching reading. This is in fact in line with some empirical evidence of the importance of the SQ4R method as one of the effective ways to enhance EFL learners ' reading comprehension (Alzu'bi, 2020;Ginting et al, 2021;Khusniyah, 2020;Mohamed Sayed Mohamed, 2020;Nurhidayat & Suwandi, 2021;Başar & Gürbüz, 2017;Khusniyah & Lustyantie, 2017;Herwanis et al, 2021;Simbolon et al, 2020;Rojabi, 2020). Qualitatively, EFL learners under study experienced EFL reading comprehension process by stepping into six phases, i.e., survey, question, read, recite, relate and review.…”
Section: Discussionsupporting
confidence: 85%
“…One of the effective strategies for reading is SQ4R. Numerous studies claimed that the SQ4R strategy can be used as an effective way to enhance EFL learners ' reading comprehension (Alzu'bi, 2020;Ginting et al, 2021;Khusniyah, 2020;Mohamed Sayed Mohamed, 2020;Nurhidayat & Suwandi, 2021;Başar & Gürbüz, 2017;Khusniyah & Lustyantie, 2017;Herwanis et al, 2021;Simbolon et al, 2020;Rojabi, 2020). In the SQ4R strategy, learners are not only required to increase reading comprehension by conventional ways in which learners are recognizing global ideas and detailed linguistic features in the text, but also enhance their critical competence where intellectual indigestion is optimized.…”
Section: Introductionmentioning
confidence: 99%
“…Other predecessor study had been carried out by Khusniyah (2020) to reveal Teacher's Perception on SQ4R in English Reading Comprehension Learning Using Zoom Application. The result showed that the use of zoom in learning English especially in reading comprehension gives positive attitude.…”
Section: Literary Reviewmentioning
confidence: 99%
“…Then, Research results related to interest in learning can be improved in various ways. For example, the study results found the benefits acquired from the utilization of infographics, reducing the students' boredom, increasing their will to read, and developing their ability to think critically and organize ideas (Meialldy, 2021), smartphones (Narulita Mahendra, 2020), SQ4R (Alzu'bi, 2020), (Amanvermez İncirkuş & Beyreli, 2020), (Başar & Gürbüz, 2017) or using of Zoom Application (Khusniyah, 2020).…”
Section: ▪ Results and Disscussionmentioning
confidence: 99%